An effectiveness of EEG signal based on body earthing application - Zarith Liyana, Zahari; Mahfuzah, Mustafa; Noor Aisyah, Ab Rahman; Rafiuddin, Abdubrani; Zaridah, Mat Zain (Indonesian Society for Knowledge and Human Development, 2022)
Stress is part of the social lifestyle, intellectual level, and emotional strain. Stress psychology contributions include mental, cognitive, or behavioral sensation. In summative assessments of body earthing, the grounded person is less anxious and more comfortable in everyday activity because the Earth's potential becomes an intermediary to reduce a negative electrode compliment from the body to the Earth's surface when the body is grounded condition. The balanced electrode amounts in the human body could reduce anxiety, depression, and sleep disorders. This investigation analyzes the EEG signal in the frequency domain and time-frequency domain analysis based on body earthing application in ten electrode placements with a range of EEG frequency bands; Theta, Beta, and Alpha. The Power Spectrum Density (PSD) and Short Time Fourier Transformation (STFT), and Continuous Wavelet Transformation (CWT) have been used to determine the power and energy value. The theta frequency band result shows an increasing power and energy value of EEG signal after applying the body earthing application. However, the alpha frequency band influences the left area's EEG signal efficiency while the right parts beta frequency band is affected. The best classification performance is gained from Levenberg-Marquat neural network and Scale Conjugate Gradient technique for grading into stress index classes.